The Cerebellum Is Related to Cognitive Dysfunction in White Matter Hyperintensities - Cao, Shanshan; Nie, Jiajia; Zhang, Jun; Chen, Chen; Wang, Xiaojing; Liu, Yuanyuan; Mo, Yuting; Du, Baogen; Hu, Yajuan; Tian, Yanghua; Wei, Qiang; Wang, Kai (Frontiers in Aging Neuroscience, 2021)
Objective: White matter hyperintensity (WMH) on MRI is frequently presumed to be secondary to cerebral small vessel disease (CSVD) and associated with cognitive decline. The cerebellum plays a key role in cognition and has dense connections with other brain regions. Thus, the aim of this study was to investigate if cerebellar abnormalities could occur in CSVD patients with WMHs and the possible association with cognitive performances. Methods: A total of 104 right-handed WMH patients were divided into the mild WMH group (n = 39), moderate WMH group (n = 37), and severe WMH group (n = 28) according to the Fazekas scale, and 36 healthy controls (HCs) matched for sex ratio, age, and education years, and acquired resting-state functional MRI (rs-fMRI). Analysis of voxel-based morphometry (VBM) of gray matter volume and seed-to-whole-brain functional connectivity (FC) was performed from the perspective of the cerebellum, and their correlations with neuropsychological variables were explored. Results: The analysis revealed a lower gray matter volume in the bilateral cerebellum lobule VI and decreased FC between the left- and right-sided cerebellar lobule VI with the left anterior cingulate gyri in CSVD patients with WMH. Both changes in structure and function were correlated with cognitive impairment in patients with WMHs. Conclusion: Our study revealed damaged grey matter volume (GMV) and FC in the cerebellum associated with cognitive impairment. This indicates that the cerebellum may play a key role in the modulation of cognitive function in CSVD patients with WMHs.